SUSPECTED PORCINE REPRODUCTIVE AND RESPIRATORY SYNDROME WITH SECONDARY STAPHYLOCOCCUS SP. INFECTION IN PIGS: A CASE STUDY - Alpaini, Muhammad; Utami, Yeocelin Meida; Berata, I Ketut; Suardana, Ida Bagus Kade; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2026)
The pig farming industry in Indonesia plays an important role in the economy and food security. However, infections caused by the Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) and secondary infections by bacteria such as Staphylococcus sp. often threaten the health of pigs and farm productivity. This study aims to analyze PRRSV infections and secondary infections by Staphylococcus sp. in pigs through clinical, histopathological, and bacteriological approaches. The research method uses a qualitative approach, focusing on data collection in the form of signalments, anamnesis, epidemiological data, clinical signs, and laboratory examination of a sample taken from a pig farm in Gianyar, which was subsequently analyzed descriptively. The observed clinical findings in the case animal included diarrhea, malnutrition with BCS-1, stunted growth (dwarfism), anorexia, lethargy, dyspnea, paddling before death, and lesions at several body sites. Histopathological examination revealed hemorrhagic et necrotizing meningoencephalitis, tracheitis, myocarditis et edematous, hemorrhagic et necrotizing bronchopneumonia, hemorrhagic hepatitis, lymphoid depletion, hemorrhagic et necrotizing glomerulonephritis with glomerular atrophy, gastritis, enteritis with mucosal erosion, typhlitis and necrosis, and hemorrhagic colitis with mucosal erosion. Bacteriological examination identified Staphylococcus sp. pathogenic bacterium. Based on clinical analysis, anatomical pathology, histopathology, and bacteriology, the pig in question is suspected to be infected with the PRRSV with a secondary infection by Staphylococcus sp. pathogen. Animal health management practices, especially PRRSV vaccination and proper herd management, are critical to reduce the risk of secondary infections by bacteria like Staphylococcus sp. Further research, particularly molecular Polymerase Chain Reaction (PCR) testing, is required to confirm the diagnosis.